Representasi Sosial Komunitas Pesantren Tentang Makna Kedamaian - Ade Hidayat; Asep Sujana; Henri Henriyan Al Gadri (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
This study is aimed to describe about the meaning of peace in mental representation perspective in every member of Pesantren community, then every meaning that comes up will configurate social representation of Pesantren community about the meaning of peace, and at the final it produces inductively a whole definition about the meaning of peace that is accustomed with cultural-spiritual context of Indonesian people. The method that is used in this study is descriptive research with qualitative approach which the subject is taken based on criteria that have been set. The data retrieval is by open questionnaire using word-associating method and completed with interview. The results of this study are four categories of peaceful meaning: 1) personal piety (muru’ah); 2) hospitality (silaturahmi); 3) civil society (madani); and 4) a mercy to the worlds (rahmatan lil alamin). Based on the study result, it can be recognized that objectivication of peace in Pesantren community is a peace based on religious orders, and the anchoring of peace is a religious path as a representation of Islamic teaching as the mercy to the worlds (rahmatan lil alamin) that emphasize life harmony where it starts from individual improvement (intrapersonal) to interpersonal quality life, society, and also to the brotherhood of all mankind, till implemented world without violence, world with justice that appreciate freedom and equity can be realized.